Memorial acadêmico: uma estudante indígena no curso de terapia ocupacional: reflexões e contribuições para o povo indígena Atikum-Umã - Oliveira, Taís Maria de (Universidade Federal de São Carlos, 2023)
This academic memorial aims to present my experiences during the Federal University of São Carlos, SP Occupational Therapy course as a final requirement for acquiring a bachelor’s degree in occupational therapy. I intend to reflect on my experiences in higher education, especially in the formative path along the obligatory professional internships in different areas of occupational therapy, which contributed to my personal and professional formation, as an indigenous student of the Atikum-Umã People, from the city of Mirandiba-PE, Brazil.
Academic memorial: an indigenous student in the occupational therapy course: reflections on contributions to the indigenous people Atikum-Umã
Keywords: Povo Atikum-Umã; Estágio profissional; Experiência prática; Cultura; Terapia ocupacional; Memorial; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL